2007
DOI: 10.1186/1471-2318-7-15
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of fall incidents in patients with a high risk of falling: design of a randomised controlled trial with an economic evaluation of the effect of multidisciplinary transmural care

Abstract: BackgroundAnnually, about 30% of the persons of 65 years and older falls at least once and 15% falls at least twice. Falls often result in serious injuries, such as fractures. Therefore, the prevention of accidental falls is necessary. The aim is to describe the design of a study that evaluates the efficacy and cost-effectiveness of a multidisciplinary assessment and treatment of multiple fall risk factors in independently living older persons with a high risk of falling.Methods/DesignThe study is designed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 41 publications
0
16
1
3
Order By: Relevance
“…We compared the results of previous systematic reviews on the clinical effects of occupational therapy for older people. With regard to findings on fall prevention (Peeters et al, ), there is strong evidence that certain exercise programmes may help prevent falls. Both individual home‐based and group exercise classes reduce the rate and risk of falling, as do home safety interventions.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the results of previous systematic reviews on the clinical effects of occupational therapy for older people. With regard to findings on fall prevention (Peeters et al, ), there is strong evidence that certain exercise programmes may help prevent falls. Both individual home‐based and group exercise classes reduce the rate and risk of falling, as do home safety interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The design of this study was published in detail elsewhere. 31 In short, this was a randomized controlled trial with 1-year follow-up ( Figure 1). The study was conducted from April 3, 2005, to July 21,2008.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…11 Recently, a randomized controlled trial demonstrated that implementation of multidisciplinary assessment followed by treatment of fall risk factors could reduce the incidence of falls in independently living persons of 65 years and older. 12 Finally, it has been reported that arrhythmias may be responsible for unexplained syncope in older patients. An implantable loop recorder has revealed several cases of brady-tachy arrhythmias as cause of syncope in the elderly.…”
Section: Case Reportmentioning
confidence: 99%